A Study of Leadership of Head Nurse in Management for Generation Y Nurses - คุณพูล ภรณ์ทิพย์; วิวัฒน์วานิช สุวิณี (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this descriptive research was A study of leadership of head nurse in management for generation Y nurses, The Delphi Technique was used in this study. Participant were nineteen experts, including three nursing administrators, five head nurses, one human resources planning administrator, four academic institutions and instructor who teaching in nursing administration, and six generation Y nurses. The Delphi technique consisted of 3 steps. Step 1, all experts were described about the leadership of head nurse in management for generation Y nurses. Step 2, used data from step 1 to be analyzed by using content analysis for developing the rating scales questionnaire. All items in the questionnaire were ranked the level of the leadership of head nurses by a prior panel of experts. Step 3, data were analyzed by using median and interquartile range which was developed a new version of the questionnaire. The new questionnaire was sent to previous experts to confirm the previous ranked items. Data were analyzed again by median and interquartile range to summarize the study.The results of the study were presented that the leadership of head nurse in management for generation Y nurses, consisted of 8 components resulting in 78 items. They were: 1) Attributes 21 items, 2) Vision 8 items, 3) Inspiration 12 items, 4) Service 6 items, 5) Development 11 items, 6) Conflict Management 4 items,7)Supervision 7 items, and 8)Information technology and communications 9 items.